Causation In International Relations - KURKI, Milja (Cambridge University Press, 2008)
World political processes, such as wars and globalisation, are engendered by complex sets of causes and conditions. Although the idea of causation is fundamental to the field of International Relations, what the concept of cause means or entails has remained an unresolved and contested matter. In recent decades ferocious debates have surrounded the idea of causal analysis, some scholars even questioning the legitimacy of applying the notion of cause in the study of International Relations. This book suggests that underlying the debates on causation in the field of International Relations is a set of problematic assumptions (deterministic, mechanistic and empiricist) and that we should reclaim causal analysis from the dominant discourse of causation. Milja Kurki argues that reinterpreting the meaning, aims and methods of social scientific causal analysis opens up multi-causal and methodologically pluralist avenues for future International Relations scholarship.